To find the total cost \( y \) in terms of the number of kites purchased \( x \), we can formulate the equation based on your pricing structure.
You charge $6 for each kite and a flat shipping fee of $10. Therefore, the equation for the total cost can be expressed as:
\[ y = 6x + 10 \]
Where:
- \( y \) is the total cost,
- \( x \) is the number of kites purchased.
Next, let's complete the table with different values for kites purchased:
| Kites Purchased (\( x \)) | Total Cost for Kites-R-Fun (\( y \)) | |-----------------------------|---------------------------------------| | 0 | \( y = 6(0) + 10 = 10 \) | | 1 | \( y = 6(1) + 10 = 16 \) | | 4 | \( y = 6(4) + 10 = 34 \) | | 7 | \( y = 6(7) + 10 = 52 \) | | 10 | \( y = 6(10) + 10 = 70 \) |
So, the completed table will look like this:
| Kites Purchased | Total Cost for Kites-R-Fun | |----------------|------------------------------| | 0 | $10 | | 1 | $16 | | 4 | $34 | | 7 | $52 | | 10 | $70 |